Health Compromising Behaviors by Gender among Florida Adolescents - Theophile Niyonsenga; WayWay M. Hlaing; Kelli R. McCormack Brown (University of North Florida, 2008)
The current study examined the differences in prevalence and correlates of three health compromising behaviors (lifetime alcohol use, illicit drug use, and risky sexual behaviors) among male and female adolescents. Secondary analysis of the Florida Youth Risk Behavior Survey (YRBS) was performed. Multivariable logistic regression models that assessed the probability of each behavior were fitted separately for each gender. There were 1828 males and 2025 females (n=3,853). Prevalence of frequent use of all substances (alcohol and illicit drugs) was higher among males than females. Common correlates of all three health compromising behaviors included age group, grade level, delinquent behaviors, forced sexual intercourse, and age of first sexual intercourse. However, association between delinquent and sexual risk behaviors was significant only among males. In prevention of risk and promotion of healthy behaviors among adolescents, underlying differences between genders and other variations should be considered.